How to prevent and address safeguarding concerns in global health research programmes: practice, process and positionality in marginalised spaces. Issue 5 (13th May 2020) - Aktar, Bachera; Alam, Wafa; Ali, Samiha; Awal, Abdul; Bayoh, Margaret; Chumo, Ivy; Contay, Yirah; Conteh, Abu; Dean, Laura; Dobson, Skye; Edstrom, Jerker; Elsey, Helen; et al.
Abstract : Safeguarding is rapidly rising up the international development agenda, yet literature on safeguarding in related research is limited. This paper shares processes and practice relating to safeguarding within an international research consortium (the ARISE hub, known as ARISE). ARISE aims to enhance accountability and improve the health and well-being of marginalised people living and working in informal urban spaces in low-income and middle-income countries (Bangladesh, India, Kenya and Sierra Leone). Our manuscript is divided into three key sections. We start by discussing the importance of safeguarding in global health research and consider how thinking about vulnerability as a relational concept (shaped by unequal power relations and structural violence) can help locate fluid and context specific safeguarding risks within broader social systems. We then discuss the different steps undertaken in ARISE to develop a shared approach to safeguarding: sharing institutional guidelines and practice; facilitating a participatory process to agree a working definition of safeguarding and joint understandings of vulnerabilities, risks and mitigation strategies and share experiences; developing action plans for safeguarding. This is followed by reflection on our key learnings including how safeguarding, ethics and health and safety concerns overlap; the challenges of referral and support for safeguarding concerns within frequently underserved informal urban spaces; and the importance of reflective practice and critical thinking about power, judgement and positionality and the ownership of the global narrative surrounding safeguarding. We finish by situating our learning within debates on decolonising science and argue for the importance of an iterative, ongoing learning journey that is critical, reflective and inclusive of vulnerable people.